Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Discover a wealth of knowledge from professionals across various disciplines on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To solve the expression [tex]\((7m - 5n)^3 - (7m + 5n)^3\)[/tex], let's approach it step by step using algebraic manipulation and known identities.
### Step 1: Recognize the Cubes Difference Identity
The expression [tex]\((a)^3 - (b)^3\)[/tex] can be factored using the difference of cubes identity:
[tex]\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \][/tex]
where [tex]\(a = 7m - 5n\)[/tex] and [tex]\(b = 7m + 5n\)[/tex].
### Step 2: Apply the Identity
Substitute [tex]\(a = 7m - 5n\)[/tex] and [tex]\(b = 7m + 5n\)[/tex] into the difference of cubes identity:
[tex]\[ (7m - 5n)^3 - (7m + 5n)^3 = ((7m - 5n) - (7m + 5n))((7m - 5n)^2 + (7m - 5n)(7m + 5n) + (7m + 5n)^2) \][/tex]
### Step 3: Simplify the First Term
Calculate [tex]\((7m - 5n) - (7m + 5n)\)[/tex]:
[tex]\[ (7m - 5n) - (7m + 5n) = 7m - 5n - 7m - 5n = -10n \][/tex]
### Step 4: Simplify the Second Term
Next, we need to simplify the expression inside the parentheses:
[tex]\[ (7m - 5n)^2 + (7m - 5n)(7m + 5n) + (7m + 5n)^2 \][/tex]
Calculate each part separately:
1. [tex]\((7m - 5n)^2\)[/tex]:
[tex]\[ (7m - 5n)^2 = (7m)^2 - 2 \cdot 7m \cdot 5n + (5n)^2 = 49m^2 - 70mn + 25n^2 \][/tex]
2. [tex]\((7m - 5n)(7m + 5n)\)[/tex]:
[tex]\[ (7m - 5n)(7m + 5n) = (7m)^2 - (5n)^2 = 49m^2 - 25n^2 \][/tex]
3. [tex]\((7m + 5n)^2\)[/tex]:
[tex]\[ (7m + 5n)^2 = (7m)^2 + 2 \cdot 7m \cdot 5n + (5n)^2 = 49m^2 + 70mn + 25n^2 \][/tex]
### Step 5: Combine the Parts
Add the three parts together:
[tex]\[ (49m^2 - 70mn + 25n^2) + (49m^2 - 25n^2) + (49m^2 + 70mn + 25n^2) \][/tex]
Combine like terms:
[tex]\[ 49m^2 - 70mn + 25n^2 + 49m^2 - 25n^2 + 49m^2 + 70mn + 25n^2 = 147m^2 + 25n^2 \][/tex]
### Step 6: Put All Together
So, the simplified form of the expression is:
[tex]\[ (7m - 5n)^3 - (7m + 5n)^3 = -10n (147m^2 + 25n^2) \][/tex]
### Final Simplified Form
This yields the final expression as:
[tex]\[ -1470m^2n - 250n^3 \][/tex]
Thus, the fully simplified result for [tex]\((7m - 5n)^3 - (7m + 5n)^3\)[/tex] is:
[tex]\[ -1470m^2n - 250n^3 \][/tex]
### Step 1: Recognize the Cubes Difference Identity
The expression [tex]\((a)^3 - (b)^3\)[/tex] can be factored using the difference of cubes identity:
[tex]\[ a^3 - b^3 = (a - b)(a^2 + ab + b^2) \][/tex]
where [tex]\(a = 7m - 5n\)[/tex] and [tex]\(b = 7m + 5n\)[/tex].
### Step 2: Apply the Identity
Substitute [tex]\(a = 7m - 5n\)[/tex] and [tex]\(b = 7m + 5n\)[/tex] into the difference of cubes identity:
[tex]\[ (7m - 5n)^3 - (7m + 5n)^3 = ((7m - 5n) - (7m + 5n))((7m - 5n)^2 + (7m - 5n)(7m + 5n) + (7m + 5n)^2) \][/tex]
### Step 3: Simplify the First Term
Calculate [tex]\((7m - 5n) - (7m + 5n)\)[/tex]:
[tex]\[ (7m - 5n) - (7m + 5n) = 7m - 5n - 7m - 5n = -10n \][/tex]
### Step 4: Simplify the Second Term
Next, we need to simplify the expression inside the parentheses:
[tex]\[ (7m - 5n)^2 + (7m - 5n)(7m + 5n) + (7m + 5n)^2 \][/tex]
Calculate each part separately:
1. [tex]\((7m - 5n)^2\)[/tex]:
[tex]\[ (7m - 5n)^2 = (7m)^2 - 2 \cdot 7m \cdot 5n + (5n)^2 = 49m^2 - 70mn + 25n^2 \][/tex]
2. [tex]\((7m - 5n)(7m + 5n)\)[/tex]:
[tex]\[ (7m - 5n)(7m + 5n) = (7m)^2 - (5n)^2 = 49m^2 - 25n^2 \][/tex]
3. [tex]\((7m + 5n)^2\)[/tex]:
[tex]\[ (7m + 5n)^2 = (7m)^2 + 2 \cdot 7m \cdot 5n + (5n)^2 = 49m^2 + 70mn + 25n^2 \][/tex]
### Step 5: Combine the Parts
Add the three parts together:
[tex]\[ (49m^2 - 70mn + 25n^2) + (49m^2 - 25n^2) + (49m^2 + 70mn + 25n^2) \][/tex]
Combine like terms:
[tex]\[ 49m^2 - 70mn + 25n^2 + 49m^2 - 25n^2 + 49m^2 + 70mn + 25n^2 = 147m^2 + 25n^2 \][/tex]
### Step 6: Put All Together
So, the simplified form of the expression is:
[tex]\[ (7m - 5n)^3 - (7m + 5n)^3 = -10n (147m^2 + 25n^2) \][/tex]
### Final Simplified Form
This yields the final expression as:
[tex]\[ -1470m^2n - 250n^3 \][/tex]
Thus, the fully simplified result for [tex]\((7m - 5n)^3 - (7m + 5n)^3\)[/tex] is:
[tex]\[ -1470m^2n - 250n^3 \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.